Fluid replacement during marathon running - Noakes, T. (Clinical Journal of Sport Medicine, 2003)
During endurance exercise, about 75% of the energy produced from metabolism is in the form of heat, which cannot accumulate. The remaining 25% of energy available can be used for movement. As running pace increases, the rate of heat production increases. Also, the larger one's body mass, the greater the heat production at a particular pace. Sweat evaporation provides the primary cooling mechanism for the body, and for this reason athletes are encouraged to drink fluids to ensure continued fluid availability for evaporation and circulatory flow to the tissues. Elite level runners could be in danger of heat illness if they race too quickly in hot/humid conditions and may collapse at the end of their event. Most marathon races are scheduled at cooler times of the year or day, however, so that heat loss to the environment is adequate. Typically, this postrace collapse is due simply to postural hypotension from decreased skeletal muscle massage of the venous return circulation to the heart on stopping. Elite athletes manage adequate hydration by ingesting about 200-800 mL/hour, and such collapse is rare. Athletes "back in the pack" are moving at a much slower pace, however, with heat accumulation unlikely and drinking much easier to manage. They are often urged to drink "as much as tolerable," ostensibly to prevent dehydration from their hours out on the race course. Excessive drinking among these participants can lead to hyponatremia severe enough to cause fatalities. A more reasonable approach is to urge these participants not to drink as much as possible but to drink ad libitum (according to the dictates of thirst) no more than 400-800 mL/hour.